2010
DOI: 10.1007/s11250-010-9765-1
|View full text |Cite
|
Sign up to set email alerts
|

Nutrients intake, digestibility, nitrogen balance and growth performance of sheep fed different silages with or without concentrate

Abstract: The experiment was conducted to investigate the influence of maize (Zea mays), sorghum (Sorghum bicolor) and millet (Pennisetum americannum) silages with or without concentrate on nutrients intake, digestibility, nitrogen balance and weight gain in Sipli sheep. Six experimental diets were formulated having 100% maize silage (MS), maize silage and concentrate as 50:50 (MSC), 100% sorghum silage (SS), sorghum silage and concentrate as 50:50 (SSC), 100% millet silage (MiS) and millet silage and concentrate as 50:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
14
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 26 publications
4
14
0
Order By: Relevance
“…These findings are in agreement with Petit and Castonguay (1994). Similar trend was observed by Khan et al (2011) who found that DMI ranged between 1.050 to 1.225 kg/d of different types of silage with or without concentrate, as well as feed conversion ratio ranged between 6.67 and 8.75 with significant differences among rations. Abdul-Aziz et al (1999) calculated feed conversion of 8.30 and 9.50 kg DMI/kg gain of growing Barky lambs fed either BH plus CFM or halophytic silage plus CFM, respectively.…”
Section: Growth Performance Of Lambssupporting
confidence: 91%
See 1 more Smart Citation
“…These findings are in agreement with Petit and Castonguay (1994). Similar trend was observed by Khan et al (2011) who found that DMI ranged between 1.050 to 1.225 kg/d of different types of silage with or without concentrate, as well as feed conversion ratio ranged between 6.67 and 8.75 with significant differences among rations. Abdul-Aziz et al (1999) calculated feed conversion of 8.30 and 9.50 kg DMI/kg gain of growing Barky lambs fed either BH plus CFM or halophytic silage plus CFM, respectively.…”
Section: Growth Performance Of Lambssupporting
confidence: 91%
“…Petit and Castonguay (1994) found that ADG and feed efficiency of cross-breed lambs were significantly greeter when fed grass silage plus CFM than those fed grass silage only (ad libitum). Similar results were reported by Khan et al (2011) when they used corn silage with or without concentrate. On contrary, Mustafa et al (2008) observed that cross-breed lambs fed CFM ad libitum plus 100 g grass hay gained significantly higher than those fed ray grass silage ad libitum plus 100-450 g CFM (382 vs. 109 g/d).…”
Section: Growth Performance Of Lambssupporting
confidence: 88%
“…Live weight gains were low in lambs fed only silage diets and inclusion of grain to the diet led to good responses in production parameters (1). The cereals are of certain interest because of extensive use for hay production.…”
Section: Introductionmentioning
confidence: 99%
“…The similarity in concentrations of fibre fractions in silage generated from the current work as compared with other trials carried out around the world resulted in almost the same consumption of NDF and ADF as described by Khan et al . (2011), who reported intake of 586 g (±17·1) NDF/day in animals weighing 30 kg ± 4·45. The average NDF intake as a percentage of BW (2·8%) was higher than that shown by dos Santos et al .…”
Section: Discussionmentioning
confidence: 99%
“…The ratio of N intake to N absorbed in the present study was similar to that observed in Sipli lambs (0·51) fed pearl millet cultivars grown in semi-arid zones in Pakistan as evidenced by Khan et al . (2011). It should be mentioned that the positive N balance and lack of body reserve mobilization observed in all the lambs fed on the Brazilian pearl millet cultivars suggests an adequate digestibility of dietary protein.…”
Section: Discussionmentioning
confidence: 99%